Monitoring and monetary incentives in addressing absenteeism: Evidence from a sequence of policy changes - Francesco D'Amuri (University of Essex, Institute for Social and Economic Research (ISER), 2011)
Exploiting three variations in sickness absence policy for civil servants in Italy, this paper assesses the importance of monitoring and monetary incentives in addressing absenteeism. Sickness absence is sensitive to monitoring intervals for random inspections, while moderate monetary incentives are relatively less effective. Results are not driven by attenuation bias, while a falsification test shows that, out of the 13 semesters analysed in this study, the only significant changes in relative public/private sector absence rates were observed in the three semesters in which stricter monitoring determined substantial increases in attendance.
Keywords: J32; J38; J45; 330; monetary incentives; monitoring; effort; sickness absence; Öffentlicher Dienst; Krankheit; Arbeitskräfte; Fehlzeit; Kontrolle; Ökonomischer Anreiz; Italien